Multidisciplinary Simulation for Blunt and Penetrating Pediatric Trauma Utilizing Standard and Rapid Cycle Deliberate Practice Models - Erin B. Henkel; Daniel Lemke; Daniel Rubalcava; Bindi Naik-Mathuria; Katherine M. Gautreaux; Jeannie Eggers; Cara Doughty (MedEdPORTAL, 2024)
Introduction Pediatric trauma resuscitations are low-frequency, high-stakes events that require skilled multidisciplinary teams with strong medical knowledge and communication skills. Methods This pediatric trauma simulation training session included two cases and formats. The first case was designed in a traditional format and featured a 12-month-old child with inflicted blunt head and abdominal trauma. The second case was organized in successive rounds utilizing the rapid cycle deliberate practice (RCDP) model and featured an 18-month-old with gunshot wounds to the abdomen and chest. Educational objectives included effective communication in a multidisciplinary team, timely completion of primary and secondary surveys, awareness of systems and processes related to trauma care, and increasing competency with low-frequency pediatric trauma skills. Necessary equipment included high-fidelity toddler-sized mannequins, chest tube task trainer or applicable mannequin and equipment, intubation equipment and supplies, intraosseous access, and blood products with rapid delivery infusers. This training session was designed for learners in a multidisciplinary team including physician trainees, nurses, and advanced practice providers; adjustments could be made to the team members as desired. Results Quantitative and qualitative evaluations demonstrated high learner satisfaction and engagement, particularly in the RCDP style of learning. Discussion Multidisciplinary team practice of pediatric trauma scenarios, particularly utilizing the RCDP simulation model, provides the opportunity to improve teamwork and communication, practice procedural skills, and deepen team members' understanding of and comfort with trauma resuscitations.